2015
DOI: 10.1142/s0218216515410060
|View full text |Cite
|
Sign up to set email alerts
|

A parity map of framed chord diagrams

Abstract: We consider framed chord diagrams, i.e. chord diagrams with chords of two types. It is well known that chord diagrams modulo 4T-relations admit Hopf algebra structure, where the multiplication is given by any connected sum with respect to the orientation. But in the case of framed chord diagrams a natural way to define a multiplication is not known yet. In the present paper, we first define a new module M 2 which is generated by chord diagrams on two circles and factored by 4T-relations. Then we construct a "p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…However (see the discussion in [15]), for a certain time it was supposed that the framed chord diagrams modulo these relations do not form a bialgebra. And indeed, it was shown recently by Ilyutko and Manturov in [13]. In a similar way each multicomponent plane curve with self-tangencies gives rise to a ribbon graph.…”
Section: 3mentioning
confidence: 64%
See 2 more Smart Citations
“…However (see the discussion in [15]), for a certain time it was supposed that the framed chord diagrams modulo these relations do not form a bialgebra. And indeed, it was shown recently by Ilyutko and Manturov in [13]. In a similar way each multicomponent plane curve with self-tangencies gives rise to a ribbon graph.…”
Section: 3mentioning
confidence: 64%
“…Unfortunately, this fails even on the stage of framed chord diagrams (one-vertex ribbon graphs, not necessarily orientable), modulo the four-term relation. As it was discussed in [15] and shown in [13], the attempt to multiply framed chord diagrams in a similar way as in the previous subsection fails: this multiplication is not well-defined. (Recently M. Karev [14] showed that framed chord diagrams form a module over the bialgebra of chord diagrams.…”
Section: 3mentioning
confidence: 88%
See 1 more Smart Citation
“…It was asked in [14] whether imposing the 4-term relations allows one to define multiplication on framed chord diagrams as well. Recently, D. P. Ilyutko and V. O. Manturov [10] answered this question in negative. The results of the present section show, however, that on the level of (binary) delta-matroids we obtain Hopf algebra structures not only for framed chord diagrams, but for arbitrary embedded graphs as well.…”
Section: Four-term Relationsmentioning
confidence: 99%
“…2 Framed chord diagrams Definition 2.1 ( [8,10]). A chord diagram is a cubic graph consisting of a selected oriented Hamiltonian cycle (the core circle) and several non-oriented edges (chords) connecting points on the core circle.…”
Section: Introductionmentioning
confidence: 99%